Infrastructure of Geospatial Data in Ukraine: Status and Methodological Problems of Legislative Regulation - Dyshlyk, O.; Dorosh, A.; Tarnopolsky, A.; Tarnopolsky, Ye. (Land Management, Cadastre and Land Monitoring, 2018)
According to World Bank experts, the basis for a wise state and municipal policy is a high-quality information about the territory and access to it by public authorities, i.e. geospatial data.The success of the creation and operation of the nationalinfrastructure for geospatial data (NIGD), aimed at the development of the geospatial world for the development of the economy, the provision of vital services, the maintenance of sustainable development, improving the lives of people around the world is based on several generally accepted things in the world.The development of economics and management systems in the world increasingly depends on informative. Government, local government, society, business, citizens are increasingly demanding not just information but information that is reliable, relevant, integrated or capable of integration. Society requires the integration of spatial, statistical and administrative data, online access to them and the creation of electronic information services. Ukraine also already has a considerable experience of global initiatives in the area of geospatial data and geoinformation systems.The current state of development of geoinformation technologies requires the formation of a permanent system of topographical monitoring, which will provide the publication of geospatial data in a mode close to real time practically simultaneously with changes in the area.Based on the absence of standard documents on the establishment of such systems (Concepts, programs, specifications, technical requirements for the collection and processing of various types and types of data), city councils, in the form of a city-planning cadaster, geoinformation systems for managing property or other objects communal property increasingly create geographic information systems without any connection with the country's sectoral and corporate systems and the ideology and trends developed by the world expert environment under the UN and EU Agreements and agreed upon by Ukraine as part of these organizations.There is a need to resolve issues of legislative, institutional and financial support, and, on their basis, identify organizational measures aimed at creating and developing such an infrastructure. In conditions of developed highly professional environment, the formation of public policy regarding the field of geospatial data, the ideology of the new interdisciplinary model and its legislative regulation cannot be usurped by any professional group.Based on the analysis of world trends in the field of NIGD and UN recommendations on the ideology of constructing such systems at the national level, the state of development of NIGD in Ukraine and the status of institutional, legislative and financial support in this area are analyzed. Deviations from the UN recommendations are outlined, systemic principles of the creation of the NIGD are proposed, and a list of measures and actions for the return of the process of constructing the NIGD on the innovative way is proposed.When creating NIGD it is advisable to be guided by the following system principles: Design, not improvement; classification, not generalization; open solutions.Key words: Infrastructure, geospatial data, NIGD, NSDI, sustainable development, legislative provision, institutional provision, financial support.